2021
DOI: 10.25248/reas.e9073.2021
|View full text |Cite
|
Sign up to set email alerts
|

A influência dos hormônios sexuais na resposta imunológica da COVID-19: uma revisão integrativa

Abstract: Objetivo: Avaliar as diferenças sexuais na resposta imunológica a COVID-19 relacionadas a influência hormonal. Métodos: Foi realizada uma pesquisa bibliográfica, de caráter exploratório, do tipo revisão integrativa de literatura. A busca dos artigos foi realizada nas bases eletrônicas de dados PubMed, Biblioteca Virtual em Saúde (BVS) e Scientific Electronic Libray Online (SciELO) no período de fevereiro a maio de 2021. Foram incluídos artigos originais, publicados entre 2020 e 2021 e redigidos em português, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…As for gender, other investigators have shown higher positivity, the worst prognosis, and death outcomes for male compared to female patients [ 29 ]. Epidemiologically, one hypothesis is related to the higher level of exposure among men and a greater preventive care behavior of women with health.…”
Section: Discussionmentioning
confidence: 99%
“…As for gender, other investigators have shown higher positivity, the worst prognosis, and death outcomes for male compared to female patients [ 29 ]. Epidemiologically, one hypothesis is related to the higher level of exposure among men and a greater preventive care behavior of women with health.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that sex hormones are immunomodulators and that their different concentrations in men and women can influence the viral load of tolerant women, their clinical manifestations and their morbidity and mortality. This is because estrogen, subtype 17β-estradiol (E2), promotes a stronger immune response in women by acting on the regulation and control of T and B lymphocytes, in the recruitment of monocytes, in the exclusion of proinflammatory cytokines and in the presentation of antigens (Reis et al, 2021;Silva et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, high concentrations of estrogen decrease the availability of this enzyme. Meanwhile, low concentrations of these hormones in the body, associated with high testosterone levels, increase the expression of the enzyme and, consequently, its binding to SARS-CoV-2 (Reis et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Na Figura 2 observa-se que machos castrados tiveram maiores valores no ELISA para anticorpos contra o SARS-CoV-2. Os hormônios sexuais possuem uma influência direta no controle e desenvolvimento de resposta imunológica (REIS et al, 2021). A testosterona tem uma característica imunossupressora, podendo levar a uma limitada resposta pró-inflamatória, por sua vez a progesterona e o estradiol desenvolvem um papel modulador do sistema imune suprimindo a capacidade de resposta (VÁZQUEZ-MARTÍNEZ et al, 2018), desta forma machos castrados podem sofrer menores influências dos hormônios sexuais na sua capacidade de resposta imune.…”
Section: Númerounclassified